Reflections on twenty-five years of landscape ecology discussion in the German-speaking IALE community - Werner Rolf; Uta Schirpke (Landscape Online)
In May 1999, about 30 people from Austria, Germany and Switzerland met in Basel (Switzerland) to found the German Chapter of the International Association for Landscape Ecology (IALE-D) to bring together Germanspeaking researchers, planners and other people interested in landscape ecology. Now, twenty-five years later, we take this milestone as an opportunity to reflect on the evolution of the topics that have shaped the landscape ecology discourse within the IALE-D community. In this editorial, we (1) present the history of the IALE-D conferences, (2) reflect on the topics addressed by the conference contributions and how they have developed, and (3) offer some initial indications of changes in relevance with regard to technological advances, thematic foci, transdisciplinarity, sustainability issues, and cultural dimensions that can be observed over time. Furthermore, we provide an overview of the articles published in 2024 in Landscape Online, which mainly reflect two emerging topics, which follow the lines of the thematic development of the IALE-D conferences, that is, a focus on urban environments as well as on pressing issues related to global change.